solve 3sinh^2(2x) + 11sinh(2x) = 4 for x, giving your answer(s) in terms of the natural log.

3sinh^2(2x) + 11sinh(2x) - 4 = 0 --> (3sinh(2x) - 1)(sinh(2x) + 4) = 0 --> sinh(2x) = 1/3, sinh(2x) = -4(e^(2x) - e^(-2x))/2 = 1/3 --> e^(4x) -(2/3)e^(2x) - 1 = 0 --> e^(2x) = 1/3 + 2sqrt(5)/3 the other solution is negative, e^2x > 0--> x = (1/2)ln(1/3 + 2sqrt(5)/3)(e^(2x) - e^(-2x))/2 = -4 --> e^(4x) - 8e^(2x) - 1 = 0 --> e^(2x) = 4 + sqrt(34) sqrt(34) > 4 so other solution is negative--> x = (1/2)ln(4 + sqrt(34))

Related Further Mathematics A Level answers

All answers ▸

How do I solve a simultaneous equation with more unknowns than equations?


Find a vector that is normal to lines L1 and L2 and passes through their common point of intersection where L1 is the line r = (3,1,1) + u(1,-2,-1) and L2 is the line r = (0,-2,3) + v(-5,1,4) where u and v are scalar values.


Prove by induction that the sum from r=1 to n of (2r-1) is equal to n^2.


How do you calculate the derivative of cos inverse x?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences